The role of urban forests in CO2 sequester as an ecosystem service: Current knowledge analysis - Ahumada, Rocío A; Cantón, M Alicia; Martinez, Claudia F (BOSQUE, 2025)
Urban forests have contributed significantly to CO2 sequestration associated with photosynthesis, which mitigates the effects of climate change. The objective of this literature review was to collect and systematize the state of knowledge associated with CO2 sequestration in urban environments through a search and analysis of scientific articles in the period 2013-2023. Information systematization is structured around three axes: general information, methodologies, and obtained results. It was observed that the thematic approach presents a growing trend in Asian and North American countries in cities with different climatic characteristics, being incipient of its development for cities with arid climates in South America. The data indicate values between 0.42 and 1,901 tons per hectare of CO2 sequestered by urban forests in different climates. These values resulted from the application of specific allometric models and software, such as the Center for Urban Forestry Research’s Tree Carbon Calculator (CTCC) and i-Tree. The differences found were related to the forest condition, with the adult, perennial, and fast-growing species being the most efficient in terms of CO2 annual sequestration in relation to young, deciduous, and slow-growing species.